The Relationship of the Physical Profiles of Kick Boxers Participating in the 2019 World Championships with Their Flexibility Levels and Success Status - Pinar Tatlibal, Saadet Beyza Özer, Onur Oral (Pakistan Journal of Medical & Health Sciences, 2022)
Athletes are characterized by body composition and size characteristics that are thought to affect success in any sports branch. The aim of this study is to examine the relationship between the physical profiles and flexibility levels of elite kickboxers participating in the 2019 Senior Kickboxing World Championships and their success status. A total of 303 kickboxers (85 women and 218 men) participated in the study. The athletes who were ranked (in the first 4 athletes according to the official results) were evaluated in the group of successful athletes and those who did not enter were evaluated in the group of unsuccessful athletes. Physical profile and flexibility measurements of the athletes were made. Mean, standard deviation, minimum and maximum values were given as Descriptive Statistics of kickboxers. Statistical analyzes were evaluated with Independent Sample T Test, Mann-Whitney U Test and Pearson Correlation Analysis. Significance level was accepted as p<0.05 in the analyzes. The height of the successful male kickboxers in the kick light (KL) branch was found to be significantly higher than the unsuccessful male kickboxers (p=0.00). While the muscle mass and bone mass values of the successful male kickboxers in the KL branch were found to be significantly higher than the unsuccessful group (p=0.03; p=0.03), basal metabolism values were also higher than the unsuccessful group (p=0.03). According to the results of Pearson Correlation Analysis, a negative significant result was found between age and success in male kickboxers (r=-0.199; p<0.01).